Peningkatan Kemampuan Pemecahan Masalah Matematika Siswa Melalui Pelatihan Olimpiade Matematika Di SMPN 1 Banuhampu, Kabupaten Agam - Fathur Rahmi; Chairul Fajri; Mesi Audina Givael; Siti Noor Diana; Recy wulandari; Moh Afif Abdul Silverry; Reski Rahma Desvita; Wahyu Mahesa; Megi Agustin; Elza Fitriani (Jurnal Pengabdian Masyarakat Ilmu Keguruan dan Pendidikan (JPM-IKP), 2025)
The quality of education in Indonesia still faces various challenges, particularly in developing students' critical thinking and competitive skills in mathematics. One strategic effort to address this issue is through mathematics olympiad training, which not only enhances conceptual understanding but also fosters high-level problem-solving abilities. This study aims to evaluate the effectiveness of mathematics olympiad training in improving students' skills at SMPN 1 Banuhampu. The methods used include interactive lectures, group discussions, and olympiad problem simulations, conducted over six sessions. Evaluation was carried out by comparing participants’ pre-test and post-test scores. The results showed a significant increase in the average student score from 31.33 to 59.66. A t-test revealed a significance value of 0.000 < 0.05, indicating a positive effect of the training. Therefore, this activity is proven to be effective and can serve as a sustainable model for developing students’ mathematical competencies.